Analysis of the Impact of Public Issue ”Consortium 303” on Public Interest in Online Slot Gambling in Indonesia - Dyama Khazim Setyadi (MEDIASI : Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2023)
This study aims to analyze the impact of the 303 gambling issue on public interest in online slot gambling. This research was conducted using qualitative methods with data sources in the form of in-depth interviews with users of online slot gambling sites, online slot gambling observations on various media platforms, and documentation. The results of the study show that the issue of gambling 303 has a considerable influence on public interest in online slot gambling. On the one hand, this issue can increase user interest because they feel like trying something that is forbidden. However, on the other hand the issue of 303 gambling can also reduce user interest for fear of being involved in illegal activities. This study provides important insights into how the 303 gambling issue affects user interest in online slot gambling and can be used as a reference for developing more effective promotional strategies.